Pengaruh maqamat dalam teosofi terhadap prilaku seseorang: Dari tradisi ke peradaban milenial - Shofa, Salwa Zahira; Tunggal, Reiza Titania; Farodis, Maiya; Ismiyah, Nur Maya Munirotul; Faisol, Faisol (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the influence of maqomat in Islamic theosophy on individual behavior and explore its relevance within the context of millennial society. Maqomat refers to the spiritual stations in Sufi tradition that serve as a structured framework for inner transformation and the cultivation of moral character. Using a descriptive qualitative approach, data were collected through literature review of classical Sufi texts and in-depth interviews with individuals who embody spiritual values in modern life. The findings reveal that maqomat—such as repentance (tawbah), detachment (zuhud), patience (sabr), trust in God (tawakkul), and sincerity (ikhlas)—significantly contribute to shaping personal behavior, particularly in the aspects of self-control, integrity, social empathy, and simplicity. In the millennial context, the maqomat values are being reinterpreted and adapted through digital spirituality, minimalist lifestyles, and mindfulness practices. However, challenges arise in the form of fragmented understanding, instant spirituality, and the commodification of sacred values. This study concludes that maqomat holds substantial potential as a spiritual-ethical foundation that remains relevant amid contemporary challenges and offers a constructive contribution to building a millennial civilization that harmonizes transcendental consciousness with social reality